Repair and rehabilitation of corroded HDPE100 pipe using a new hybrid composite (Fracture and Structural Integrity, 2021)
The good management of drinking water begins with a supply network, with a low rate of leakage. Currently, the pipes used in the water transport system are mainly made of polymeric materials, such as HDPE. The corrosion degradation of this type of pipe has received a lot of attention from the drinking water supply companies. It is therefore important to understand the effect of pressure on an HDPE pipe with a surface defect. To answer this problem, we will first study the mechanical behavior at failure of HDPE pipes in the presence of a surface defect using a finite element method. For the rehabilitation of pipe in presence of surface defect, we try to use a new composite. This new laminated composite is reinforced with a natural organic load. It is obtained from a laminated composite woven by incorporating a natural non-polluting organic load (granulates of date cores) which becomes hybrid composite. The new economical hybrid composite material is made of an organic matrix containing methyl methacrylate, a woven reinforcement including a reinforcing glass fiber and a fabric perlon having an absorbing role. The textile reinforcement made up of several folds reinforcing laid out according to the orientations (90, 452, and 0). A numerical simulation with the ANSYS Workbench software is carry out  to study the behavior of the HDPE pipe with surface defect and with defect repaired by the new hybrid composite material in the form of rings to consolidate the cracked area of ​​the tube. The numerical results will allow us to decide on a real practical use of the new hybrid composite.
Keywords: Rehabilitation; pipe HDPE; superficial defect; Finite Element Method; new hybrid composite